To simulate AODV, DSR, GRP and OLSR routing protocols of VANET and study the performance indicators using Opnet Modeler 14.5 - et. al., Dr. Santosh Deshpande, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless technology is developing very fast. VANET is an evolving technology in the field of wireless communication and with the advancement it will contribute more to the smart transportation system in days to come. Quality of service in Vehicular ad-hoc Network (VANET) is primarily dependent on routing protocols. Maximum throughput, minimum packet loss and controlled overhead are the major ultimate objectives of each proposed routing protocol. VANET gives a communication framework that has enhanced the traffic service. Data sharing in this system is time sensitive and require quick and vigorous network connection forming. VANET is serving the said purposes but there are some issues and challenges like efficient handling of fast handovers for audio applications. Therefore, in this paper recently proposed routing protocols along with their pros and cons are discussed. VANET routing protocols are simulated using Opnet simulator and key performance Indicators were assessed. Simulation is performed to check the delays and throughput comparisons between the routing protocols.